Assessment of thermal comfort in the mosque in Sarawak, Malaysia - Ibrahim, S.H; Baharun, A.; Nawi, M.N.M; Junaidi, E. (International Energy & Environment Foundation, 2014)
In hot-humid climate, the mosque should be provided with an acceptable level of thermal comfort in order to seek serenity and focus for worship. The purpose of this study is to investigate the thermal comfort conditions in the Masjid Al-Muttaqin located in Kota Samarahan, Sarawak. The data were analysed using Corrected Effective Temperature (CET) index. The analysis shows that although the air velocity in the mosque is acceptable, due to the influence of high air temperature, thermal comfort is not achieved. A retrofit design by adding new materials and installing insulations on the existing roof are proposed and the results show significant improvement of thermal comfort inside the mosque.